Debatten om Grundtvig og Kierkegaard. En kristisk gennemgang - Toftdahl, Hellmut (Grundtvig-studier, 1969)
The Debate about Grundtvig and Kierkegaard.By Hellmut Toftdahl.In 19. century intellectual life Grundtvig and Kierkegaard tower like two huge antipodes: Kierkegaard’s desperation, sharpness, and merciless honesty - Grundtvig’s gigantic visions and deep understanding of the conditions and weaknesses of human life. They have left traces so profound that instead of establishing contact their imitators have widened the distance between them and made it appear as an unbridgeable gulf. Attempts to compare them have been rare: a couple of books and otherwise only short articles in newspapers and periodicals - and this although we are dealing with two works of unequalled scope in the history of Danish literature.The explanation is probably to be found in the fact that there has been no common system of reference, no third point of comparison, because the two of them seem to be complementary, i. e. they mutually complete but exclude each other. In the bulk of the existing literature about Kierkegaard and Grundtvig the approach has in fact been to condemn one of them by using the other. Only Garl Koch tries to attain objectivity by introducing Tolstoi, the Russian author, as a third point of reference, a kind of common denominator for the two others. More interest attaches to the attempt of Frederik Jungersen to make Kierkegaard an appendix to Grundtvig, an appendix emphasizing only what Grundtvig realized well enough: that the individual should not forget itself in the community. Kierkegaard stresses the self-activity of the individual, which, according to Jungersen, in Grundtvig is the basic condition of congregational life. That Jungersen is wrong here will appear from my book Kierkegaard først – og Grundtvig så, where I demonstrate how escapism, the forgetting of self, is a sine qua non in Grundtvig’s theology and view of human life. As a possible third point of reference I have called attention to the Danish author Martin A. Hansen, who overcame a Kierkegaardian crisis through Grundtvig - a crisis experienced as a conflict between humanism and Christianity, where Christianity was victorious.The article by Hinrich Buss in Kontroverse um Kierkegaard und Grundtvig is admirable. He draws a highly varied picture of the two with a criticism which is based upon objectivity and penetration. The contrast between them is clearly outlined: A Grundtvig who, on account of a not very thoroughly considered programme of secularization, has nothing to offer the present but an advice about not forgetting that the humanity of man is conditioned by his creation by God—on the other hand Kierkegaard’s “modern” analysis of existence as a paradox, carried through with inexorable passion and logical consistency. Buss sees the strength as well as the weakness in both of them: Grundtvig leaves us with the problem of being unable to attach what is human to what is Christian, carefully considered theologically; Kierkegaard performs this work, but he ends up by abandoning the human side, compelled by his dispositions. Kierkegaard is the modern thinker who places us in a situation where we can no longer avoid his reasoning. Grundtvig exhorts us not to forget the Creation; he shows us our loss if we can no longer think such thoughts as these.The article by Hinrich Buss is the first to comply with the demand, as formulated by Jørgen K. Bukdahl, to be made on a comparison between Kierkegaard and Grundtvig: they should be evaluated with regard to their place in the epoch, the period of reflection, with the attendant dissolution of given ties and the resulting “modern” presentation of the problem: How is it possible to establish authority in a reflective, civil age where the old authorities, Church, public authority, king, paterfamilias, teacher, have lost their authoritativeness?In my book Kierkegaard først - og Grundtvig så I have endeavoured to keep this period-dependence in focus, just as I have attempted to use the concepts of existentialism and phenomenology as a common system of reference, regarding, as I do, the works of the two authors as an expression of a way of having the world and an expression of the place of the ego in this subjective picture of the world. The treatises discussed and criticized in this article do not move beyond the psychologizing or the theologically systematizing sphere (vide for instance Henning Høirup, Grundtvig Studier 1956), they are accordingly atomistic, and one looks in vain for the integral person: Kierkegaard or Grundtvig, whom we expect to find behind the political, literary, or theological views expressed in their respective works. In this respect the article by Hinrich Buss is undoubtedly superior to the rest.